Marriage Registration and Its Legal Implications: A Case Study in South Coast Regency - Yuda, Yossef; Yufrizal, Yufrizal (Jurnal Kajian dan Pengembangan Umat, 2025)
This study explores the community's understanding of marriage registration and its legal implications in Pesisir Selatan Regency, Indonesia, from both positive law and Islamic law perspectives. Employing a qualitative approach with a juridical-empirical method, data were collected through interviews, observations, and documentation involving local residents, religious leaders, and officials from the Office of Religious Affairs (KUA). Referring to the Circular Letter of the Director General of Islamic Community Guidance No. 06 of 2025 on the Marriage Registration Awareness Movement, findings show that out of 163,260 registered family cards, 3,751 marriages (2.30%) remain unregistered. The majority of respondents (97.7%) demonstrated an understanding of the importance and legal basis of marriage registration as stipulated by Indonesian law. Marriage registration ensures legal certainty, promotes public welfare, and prevents potential harm (mafsadah). Although no explicit injunctions in the Qur'an or Hadith regulate marriage registration, through qiyas awlawi (analogical reasoning by priority) and the principle of maslahah mursalah (public interest), the practice is deemed to have a strong legal foundation within Islamic jurisprudence.